Optimal placement of distributed generation in distribution networks for power loss minimization and voltage profile enhancement / Maszairisam bt Ameruddin - Maszairisam, Ameruddin (2021)
Distributed generations (DGs) have emerged as an alternative to meet the growing demand of electrical energy and thus contribute to sustainable development of the nation. However, DG integration into the power system, particularly renewable energy resources such as Solar Photovoltaics (PV) and Wind Turbine (WT) introduce uncertainty in its operation due to the nature of the sources themselves. Therefore, proper planning and consideration have to be done prior to actual integration to ensure continuous supply and smooth operation of the system with minimal costs in-terms of power loss. In this regard, this research project proposes an approach for optimal placement of distributed generations in terms of renewable energy resources while satisfying the operation and technical constraints of the system such as power balance, voltage profile and lines thermal limits. The proposed approach is tested on a 33-bus radial distribution network employing the Forward and Backward Sweep Method (FBS) and Particle Swarm Optimization (PSO). Multiple scenarios are considered to show the impact of optimal location of PV and WT towards overall system performance. Finally, a complete model that integrates the performance and effectiveness of the proposed method in terms of power losses which is reduced from 10% to 40% from the base case (without DGs) and voltage profiles enhanced resulted from integration of PV and WT in the optimal locations have been demonstrated and presented.